Powder X-ray characterization of djenkolic acid - Melnikov, P.; Cuin, A.; Corbi, P. P.; Cavicchioli, M.; Massabni, Antonio Carlos [UNESP] (J C P D S-int Centre Diffraction Data, 2001)
X-ray powder diffraction data for the orthorhombic natural amino acid djenkolic acid, C7H14N2O4S2, is described in this paper. The orthorhombic cell parameters are: a = 8.12 Angstrom, b = 12.16 Angstrom, and c = 5.38 Angstrom . (C) 2001 International Centre for Diffraction Data.
Keywords: powder diffraction; djenkolic acid; amino acids